Occurrence of drug resistant bacteria in household waste samples (Stamford Journal of Microbiology, 2020)
Current study was carried out to investigate the presence of drug resistant bacterial isolates in the biodegradable household waste samples. In this respect, a total of six domestic waste samples including three kitchen waste samples and one sample each of home dust, dustbin waste and liquid waste were collected. Samples were analyzed for quantification of bacterial load and along with their drug susceptibility pattern. Huge array of total viable bacteria was present in all the samples (in average of 108 cfu/g or ml). Among the specific bacteria, Bacillus spp. was predominant and Vibrio spp. was found in almost all samples except liquid waste. Presence of Staphylococcus spp., E. coli, Klebsiella spp., Pseudomonas spp., Salmonella spp. and fecal coliform were evident in some samples. All isolates were found to be multidrug resistant. Notably, 100% resistance was documented against cefuroxime and amoxicillin. All the isolates showed sensitivity against meropenem, amikacin and ceftriaxone. Presence of drug resistant bacteria in household waste samples in present study critically raises the requirement for proper management and disposal of the accumulated domestic wastes by the municipal and government authorities.Stamford Journal of Microbiology, Vol.9(1) 2019: 15-18